First report of Stephanostomum cesticillus (Molin, 1858) Looss, 1899 in Merluccius merluccius (Linnaeus, 1758) from the Tyrrhenian Sea (Southern Italy) - De Benedetto, Giovanni; Gervasi, Claudio; Riolo, Kristian; Abbate, Jessica Maria; Natale, Sabrina; Di Paola, Davide; Falleti, Rosa; Iaria, Carmelo (Frontiers in Marine Science, 2023)
The genus Stephanostomum consists of digenean trematodes found in many marine teleosts. In this study, Stephanostomum cesticillus (Molin, 1858) Looss, 1899 metacercariae were identified in European hake (Merluccius merluccius, Linnaeus, 1758) caught in the Tyrrhenian Sea. The metacercariae were found encapsulated in the muscle, close to the spine and gills. Out of 131 specimens, 111 (P = 84.7%, mI = 25.1 mA = 21.3) were infected by digenean trematode metacercariae. Morphological and histological evaluations were carried out. The members of this genus are characterised by a double crown of spines close to the oral sucker. For identification of the parasite, molecular analysis was performed via 28S and 18S ribosomal DNA (rDNA) genes. Partial rDNA sequences of Stephanostomum highly matched to S. cesticillus for the percentage of similar identity from the nucleotide database of BLAST. The present survey reports the presence of S. cesticillus metacercariae in M. merluccius for the first time. Our results improve current knowledge on hake parasites to better understand the distribution of S. cesticillus in M. merluccius caught in the Mediterranean Sea and shed light on the life cycle of the parasite adding other possible hosts.